Densitometric evaluation of treatment effectiveness of chronic pulpitis of temporary teeth with approximal cavities by pulse-saving method (LLC "Endo Press", 2020)
One of the fundamental problems of modern dentistry is to keep the temporary teeth, namely the viability of the neurovascular bundle to the terms of the physiological change of teeth. For each of the second case of complicated forms of caries characterized by the presence of cavities on the approximal surface of the tooth. The aim of this work was to improve the condition of tissue diagnostic methods of temporary teeth with varying degrees of formation of roots. We have examined 665 children of Omsk from 3 to 8 years, of which identified a group comprising 22 people, with 29 temporary molars with cavities on the approximal surfaces with varying degrees of root formation and preliminary diagnosis of «chronic pulpitis». In the process of follow-up, according to X-ray, the degree of resorption of the roots of deciduous teeth treated for «chronic pulpitis» piloted by biological methods did not differ on the timing and nature of the flow parameters of the symmetrically disposed arranged teeth intact.